The Field of American Media Sociology: Origins, Resurrection, and Consolidation. Issue 7 (4th July 2016) - Brienza, Casey; Revers, Matthias
Abstract: This contribution is written against the backdrop of the historic dispersal of early American media sociology out from the core concerns of the discipline and into various importer academic disciplines (including communication, journalism, and media studies) and an ever‐growing pervasiveness of media in everyday life which is reflected by a resurgence of sociological scholarship in the United States since the early 2000s. The article divides the field in works that study media inwards – along the threefold dimensions of production and technologies, communication and discourse, reception and effects – and works that study media outwards. We argue that this latter perspective, examining broader theoretical, methodological, and substantive social implications of mass‐mediated communication, is the most promising one for a mature field of American media sociology. On this basis, we conclude with some suggestions regarding possible new, and as of yet understudied, lines of inquiry for future media sociologists.